Pengaruh Kualitas Pelayanan Pramuwisata Terhadap Kepuasan Wisatawan di Keraton Kasepuhan Cirebon - Hadi Mulyana; Andhika Chandra Lesmana (STIEPAR YAPARI Bandung, 2021)
This research is intended to know the influence of service quality (Reliability, Responsiveness, Assurance, Empathy and Tangibles) either partially or simultaneously to the satisfaction of customers and to know the more dominant influence from quality service. This research used quantitative method. There were 100 samples collected using accidental sampling. Collected using questioner and documentation. Instrument test is done by validity and reliability test. Multiple linear regression and classical assumption test used as analysis test. Hypothesis test is done by F test and t test. The results of the analysis show that there is an influence between service quality variables on tourist attraction of 10.30% (89.70% is influenced by other variables). What is obtained from the significance value: from the coefficients table, it is obtained a significance value of 0.001 <0.05 and t-count of 3.355> t table 1.988, so it can be concluded that the service quality variable (X) has a positive and significant effect on the tourist satisfaction variable (Y).